2001
DOI: 10.1091/mbc.12.3.739
|View full text |Cite
|
Sign up to set email alerts
|

TheChlamydomonas PF6Locus Encodes a Large Alanine/Proline-Rich Polypeptide That Is Required for Assembly of a Central Pair Projection and Regulates Flagellar Motility

Abstract: Efficient motility of the eukaryotic flagellum requires precise temporal and spatial control of its constituent dynein motors. The central pair and its associated structures have been implicated as important members of a signal transduction cascade that ultimately regulates dynein arm activity. To identify central pair components involved in this process, we characterized a Chlamydomonas motility mutant (pf6-2) obtained by insertional mutagenesis. pf6-2 flagella twitch ineffectively and lack the 1a projection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
113
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 65 publications
1
113
0
Order By: Relevance
“…5 Inset), and are associated with an almost total lack of motility (10,29). Flagella of pf6 -1 cells occasionally beat with frequencies as high as 5 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…5 Inset), and are associated with an almost total lack of motility (10,29). Flagella of pf6 -1 cells occasionally beat with frequencies as high as 5 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several subunits of dynein motors are EF-hand proteins that may bind calcium directly, altering dynein activity [Piperno et al, 1992;King and Patel-King, 1995;Yanagisawa and Kamiya, 2001;Casey et al, 2003;Guerra et al, 2003]. Chemical signaling also includes axonemal enzymes that are not directly sensitive to second messengers including casein kinase 1 (CK1), PP1, and PP2A, all of which appear to be involved in the control of dynein-driven motility [Walczak and Nelson, 1993; Central apparatus-associated polypeptides PF6 238-kDa alanine/proline rich protein; pf6 flagella lack the 1a projection on the C1 microtubule and display only twitching motion [Dutcher et al, 1984;Rupp et al, 2001] PF16 57-kDa armadillo repeat containing protein that localizes to the c1 microtubule; pf16 flagella lack the C1 microtubule and are paralyzed. PF16 may correspond to CP14 [Dutcher et al, 1984;Smith and Lefebvre, 1996] PF20 63-kDa WD-repeat containing protein that localizes to the inter-microtubule bridge connecting C1 and C2; pf20 flagella lack the entire central apparatus and are paralyzed [Adams et al, 1981;Smith and Lefebvre, 1997a] PP1c Localized primarily, but not exclusively, to the C1 microtubule [Yang et al, 2001] KLP1 83-kDa kinesin-like protein that localizes to the C2 microtubule [Bernstein et al, 1994] KRP 110-kDa kinesin related protein associated with the central apparatus, most likely the C1 microtubule [Fox et al, 1994;Johnson et al, 1994;Mitchell and Sale, 1999] AKAP240 240-kDa A-kinase anchoring protein; most likely associated with C2 [Gaillard et al, 2001] Calmodulin Most likely associated with C1, sediments as a complex at 10S [Yang et al, 2001;Dymek et al, 2002] Radial spoke-associated polypeptides RSP2 PF24 gene product, GAF, and calmodulin binding domain; pf24 mutants lack radial spoke heads and have paralyzed flagella Piperno et al, 1981;Yang et al, 2002] RSP3 PF14 gene product, 97-kDa A-kinase anchoring protein most likely localized to the base of the spokes; pf14 mutants lack radial spokes and have paralyzed flagella Piperno et al, 1981;Diener et al, 1993;Gaillard e...…”
Section: Conserved Signaling Proteins Located In the Central Pair Andmentioning
confidence: 99%
“…However, studies of Chlamydomonas rheinhardtii revealed important roles for the central apparatus. Mutant Chlamydomonas strains lacking functional PF16, PF6, and PF20 have paralyzed flagella, and the C1 microtubule, the projections connecting the C1 microtubule and the entire central pair, respectively, are missing in isolated axonemes (11)(12)(13).To understand the function of the central apparatus in mammals, we cloned the human and mouse orthologues of Chlamydomonas, PF16 (SPAG6) (14, 15) and PF20 (16). SPAG6-deficient mice are hydrocephalic, and males surviving to maturity are infertile as a result of a marked sperm motility defect associated with disorganization of flagellar structures, including loss of the central pair microtubules and disorganization of the outer dense fibers and fibrous sheath (6).…”
mentioning
confidence: 99%
“…However, studies of Chlamydomonas rheinhardtii revealed important roles for the central apparatus. Mutant Chlamydomonas strains lacking functional PF16, PF6, and PF20 have paralyzed flagella, and the C1 microtubule, the projections connecting the C1 microtubule and the entire central pair, respectively, are missing in isolated axonemes (11)(12)(13).…”
mentioning
confidence: 99%